2012
DOI: 10.1007/s10729-012-9213-z
|View full text |Cite
|
Sign up to set email alerts
|

Admission and capacity planning for the implementation of one-stop-shop in skin cancer treatment using simulation-based optimization

Abstract: Hospitals and health care institutions are facing the challenge of improving the quality of their services while reducing their costs. The current study presents the application of operations management practices in a dermatology oncology outpatient clinic specialized in skin cancer treatment. An interesting alternative considered by the clinic is the implementation of a one-stop-shop concept for the treatment of new patients diagnosed with basal cell carcinoma. This alternative proposes a significant improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 17 publications
1
45
0
1
Order By: Relevance
“…Operations management principles have been used to simulate a demand–supply model for a one‐stop skin cancer clinic and found that by managing triage criteria, resource allocation and capacity planning, the time to treatment of new patients could be reduced by 90% with the same resources (Romero et al., 2013). While modelling may be a useful first step in identifying alternative DAP designs, real‐world studies are needed to pilot the feasibility and impact of various DAP models.…”
Section: Discussionmentioning
confidence: 99%
“…Operations management principles have been used to simulate a demand–supply model for a one‐stop skin cancer clinic and found that by managing triage criteria, resource allocation and capacity planning, the time to treatment of new patients could be reduced by 90% with the same resources (Romero et al., 2013). While modelling may be a useful first step in identifying alternative DAP designs, real‐world studies are needed to pilot the feasibility and impact of various DAP models.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple authors consider the planning of flow-shop type multi-disciplinary systems, for example in oncology [23,40] and primary care practices [30]. Liang et al [23] analyze the impact of scheduling methods on the oncology clinic performance, where patients visit an oncologist and a nurse for chemotherapy treatment.…”
Section: Multi-disciplinary Schedulingmentioning
confidence: 99%
“…They included the effects of uncertainty in service time, but fixed the patient routing requirements. Romero et al [40] use simulation to evaluate different appointment scenarios in which appointment blocks are reserved for multi-disciplinary patients. This way, they prove the feasibility of a one-stop-shop for basal cell carcinoma.…”
Section: Multi-disciplinary Schedulingmentioning
confidence: 99%
See 1 more Smart Citation
“…Romero et al [73] used simulation to evaluate the implementation of a one-stop-shop in a skin cancer treatment outpatient clinic. Different scenarios of new services were analysed in the simulation model; in the best case scenario, a more than 90 per cent reduction in new patient throughput times for treatments was achievable, even at the same resource level.…”
Section: Outpatient Clinic Resource Allocationmentioning
confidence: 99%